Sinensetin suppresses influenza a virus-triggered inflammation through inhibition of NF-κB and MAPKs signalings - Jiashun Li; Xiang Jie; Xiaoli Liang; Ziyu Chen; Peifang Xie; Xiping Pan; Beixian Zhou; Jing Li (BMC, 2020)
Abstract Background Human respiratory system infected with influenza A virus (IAV) elicited a robust pro-inflammatory response that resulted in severe illness and even death. Currently, limited immunomodulator is available to counteract IAV-associated pneumonia in the clinic. Sinensetin, a polymethoxylated flavone with five methoxy groups, has been found to possess anti-agiogenesis, anti-inflammatory and anti-diabetic activities. However, the effects of sinensetin on IAV-triggered pro-inflammatory response remain unclear. In the present study, the anti-inflammatory effects and corresponding possible mechanism of sinensetin in IAV-infected A549 cells were subjected to investigations. Methods The cytotoxic effects of sinensetin towards A549 cells was detected by MTT and LDH assays. The antiviral activity of sinensetin against influenza A virus was assayed in A549 cells with an engineered replication-competent influenza A virus carrying Gaussia luciferase reporter gene infection. The effect of sinensetin on influenza A virus-triggered inflammatory reaction was determined by qRT-PCR, Luminex assays, ELISA and Western blot. Results Our results showed that sinensetin did not exhibit antiviral activity against A/PR/8/34 (H1N1). Meanwhile, sinensetin treatment significantly decreased IAV-induced expression of pro-inflammatory mediators at mRNA and protein levels, including IL-6, TNF-α, IP-10, IL-8 and MCP-1. Additionally, levels of cyclooxygenase (COX)-2 and the downstream product prostaglandin E2 (PGE2) up-regulated by IAV infection were dramatically suppressed by sinensetin. The mechanistic investigation revealed that sinensetin treatment suppressed the NF-κB transcriptional activity using the NF-κB reporter stable HEK293 cell line stimulated with TNF-α (20 ng/mL) or influenza H1N1 virus. Furthermore, sinensetin abrogated influenza H1N1 virus-induced activation of NF-κB, ERK1/2 MAPK and p38 MAPK signalings. Conclusion Collectively, our results indicated that sinensetin has potential capacity to attenuate IAV-triggered pro-inflammatory response via inactivation of NF-κB, ERK1/2 MAPK and p38 MAPK signalings, which implied that sinensetin may be a promising candidate drug for influenza H1N1 virus infection therapeutics.